The Impact of Augmented Reality on Increasing Students' Cognitive Abilities in History Learning - Hasan; Purnawati, Desak Made Oka; Herlina (Mimbar Ilmu, 2024)
Students' low cognitive abilities in understanding complex historical concepts is still a challenge in learning at school. Students' understanding is often limited to memorizing facts without being able to analyze the relationship between historical events. This condition demands innovation in learning media that is able to increase students' understanding in more depth. This research aims to evaluate the effectiveness of using Augmented Reality (AR) technology in improving students' cognitive abilities in history learning. This research uses an experimental design approach unequal control group. Data collection is carried out through initial test And post test to measure the increase in students' cognitive abilities. The research subjects consisted of two groups, namely the experimental class which used AR media and the control class which used conventional learning methods. Data analysis was carried out by comparing average scores initial test And post test in both groups and calculate the percentage increase in student learning outcomes. The research results show that the experimental class using AR technology achieved an average score post test amounted to 73.50, while the control class achieved an average score post test amounting to 65.40. Although both groups experienced an increase in initial test That post test, the experimental class showed greater improvement compared to the control class. However, student learning outcomes in the experimental class did not significantly exceed the control class. The conclusion of this research shows that AR technology can improve students' cognitive abilities in history learning by providing a more interactive and visual learning experience.